Bure Baruta - Paskaljević, Goran (Yugoslavia : Clermont-Tonnerre, Antoine de ; Paskaljević, Goran ; Vražalić, Dejan, 1998)
This dark and depressing film takes place in Belgrade in the mid 1990s and is structured along a series of violent vignettes loosely interconnected by the main characters. In one of them, an adolescent bumps into a car whose owner hunts him down, eventually trashing his father’s flat. In the next one, a middle aged guy, just back from abroad, hopes to get back his former girlfriend Natalija and indeed seems to outclass her new lover, only to end up unexpectedly drowned by him. Brutal scenes continue with a sequence in which taxi driver buys drinks for an ex-cop whom he crippled out of the revenge and another one situated in a boxing gym where two best friends confess that they have betrayed each other, and one of them butchers the other with a beer bottle. Violent episodes ensue when the killer from the previous scene finds himself on a train menacing a young woman in the compartment. The final stories focus on a Bosnian bus driver whose son works on the Black Market for a sadist, while the public bus he is suppose to drive gets kidnapped by the armed youngster who harasses the passengers.
Keywords: Fiction films